Experimental Assessment of the Electronic and Geometrical Structure of a Near-Infrared Absorbing and Highly Fluorescent Microbial Rhodopsin - Broser, Matthias; Andruniów, Tadeusz; Kraskov, Anastasia; Palombo, Riccardo; Katz, Sagie; Kloz, Miroslav; Dostál, Jakub; Bernardo, César; Kennis, John T M; Hegemann, Peter; Olivucci, Massimo; Hildebrandt, Peter (The journal of physical chemistry letters, 2023)
The recently discovered Neorhodopsin (NeoR) exhibits absorption and emission maxima in the near-infrared spectral region, which together with the high fluorescence quantum yield makes it an attractive retinal protein for optogenetic applications. The unique optical properties can be rationalized by a theoretical model that predicts a high charge transfer character in the electronic ground state (S0) which is otherwise typical of the excited state S1 in canonical retinal proteins. The present study sets out to assess the electronic structure of the NeoR chromophore by resonance Raman (RR) spectroscopy since frequencies and relative intensities of RR bands are controlled by the ground and excited state's properties. The RR spectra of NeoR differ dramatically from those of canonical rhodopsins but can be reliably reproduced by the calculations carried out within two different structural models. The remarkable agreement between the experimental and calculated spectra confirms the consistency and robustness of the theoretical approach.
Keywords: Rhodopsin; rhodopsiny mikrobiální; Spectrum Analysis, Raman; Rhodopsins, Microbial; retina; Coloring Agents; barvicí látky; Retina; rodopsin; Ramanova spektroskopie